Stages of the research on the development of legal competence of specialists in the medical sector in postgraduate education - Kharkivskyi, V. (Problems of Engineer-Pedagogical Education, 2019)
The author presents the stages of the study on the development of legal competence of medical professionals in the system of postgraduate education: the first stage (2013-2014) dealt with studying philosophical, pedagogical, medical and legal literature on the problem under investigation and implied defining the conceptual apparatus, subject, object, purpose, hypothesis and objectives of the research; the second stage (2014-2015) was dedicated to defining criteria, indicators and levels of legal competence development of medical industry specialists in the system of postgraduate education; selecting, testing and developing methodology and methods for assessing the level of the development of this competence; сonducting the indicative pedagogical stage of the experiment; analyzing the obtained data; designing a structural-functional model of the system of the legal competence development of medical industry specialists in postgraduate education; the third stage (2015-2017) dealt with introducing a structural-functional model of the system of legal competence development of medical industry specialists in postgraduate education; the fourth stage (2017-2018) was dedicated to testing the effectiveness of the implementation of this model; statistical processing of the obtained experimental data; clarifying practical conclusions; drawing up the thesis. The author comes to the conclusion that the study does not exhaust the full range of issues related to the development of legal competence of medical professionals in the system of postgraduate education. It allows us to outline the problems that need additional research, namely the problem of methodological support for managing the development of legal competence of medical professionals in the system of postgraduate education and health law in accordance with the modern requirements.